Factoring and correlation in sleep, fatigue and mental workload of clinical first-line nurses in the post-pandemic era of COVID-19: A multi-center cross-sectional study - Liu, Yan; Xian, Ji Shu; Wang, Rui; Ma, Kang; Li, Fei; Wang, Fei Long; Yang, Xue; Mu, Ning; Xu, Kai; Quan, Yu Lian; Wang, Shi; Lai, Ying; et al. (Frontiers in Psychiatry, 2022)
Background: A better understanding of the factors and their correlation with clinical first-line nurses’ sleep, fatigue and mental workload is of great significance to personnel scheduling strategies and rapid responses to anti-pandemic tasks in the post-COVID-19 pandemic era. Objective: This multicenter cross-sectional study aimed to investigate nurses’ sleep, fatigue and mental workload and their contributing factors and to determine the correlation among them. Methods: A total of 1004 eligible nurses (46 males, 958 females) from three tertiary hospitals participated in this cluster sampling survey. The Questionnaire Star online tool was used to collect the sociodemographic and study target data: Sleep quality, fatigue, and mental workload. Multi-statistical methods were used for data analysis using SPSS 25.0 and Amos 21.0. Results: The average sleep quality score was 10.545±3.399 (insomnia prevalence: 80.2%); the average fatigue score was 55.81±10.405 (fatigue prevalence: 100%); and the weighted mental workload score was 56.772±17.26. Poor sleep was associated with mental workload (r=0.303, P<0.05) and fatigue (r=0.727, P<0.01). Fatigue was associated with mental workload (r=0.321, P<0.05). COVID-19, a joint factor in both fatigue and mental workload, had a serious impact on the mental workload of 49% of the nurses and a minor impact on the sleep quality of 68.9% of the nurses. Conclusions: In the post-COVID-19 pandemic era, sleep disorders and fatigue levels among tertiary hospital nurses were higher than those of nontertiary hospitals and those during and before the virus outbreak. There was a positive interaction among sleep, fatigue and mental workload.